DEVELOPMENT OF AN ONLINE TRADEMARK INFRINGEMENT MONITORING SYSTEM: GOOGLE CASE STUDY - AYU KUMALA SARI HAMIDI; SUNNY UMMUL FIRDAUS (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2025)
Online marketing or often called digital marketing is marketing with the concept of promoting products or services through internet-based media, one of which is a website. Digital transformation has brought new opportunities and challenges to brand protection, particularly in the online space. Trademark infringement across digital platforms, including search engines like Google, is becoming increasingly common and requires innovative and integrated solutions. This article discusses the development of a technology-based monitoring system to detect and resolve online trademark infringement, focusing on a case study of Google's infringement policies and mechanisms. This research utilizes a normative legal analysis method with a case study approach. The results show that artificial intelligence (AI)-based technologies and machine learning algorithms can improve the effectiveness of infringement detection. However, challenges such as cross-country regulatory inconsistencies, lack of algorithmic transparency, and limited reporting processes remain major obstacles. The study recommends strengthening international regulations, enhancing cooperation among stakeholders, and developing comprehensive surveillance technologies to create a sustainable brand protection ecosystem in the digital age.